Tinjauan Hak-Hak Narapidana Perempuan di Lembaga Pemsyarakatan Kelas IIB Padangsidimpuan - Hanifah Mora Lubis; Padmono Wibowo (Jurnal Syntax Transformation, 2021)
The purpose of this study is to review the rights of female inmates in padangsidimpuan class IIB community institutions. The type of research used is qualitatative by using empirical juridical approach analyzing from the articles in the prevailing laws and regulations related to the facts in the field. The results showed that the implementation of services to female inmates has not been carried out properly because not all correctional officers understand and play a role in the fulfillment of the rights of female inmates, in addition to the facilities and infrastructure is still very limited so that the fulfillment of the rights of female inmates is still limited and can not be done to the maximum